Examining Latina/o Students' Experiences of Injustice: LatCrit Insights from a Texas High School. Issue 2 (3rd April 2018) - Cooper Stein, Kristy; Wright, James; Gil, Elizabeth; Miness, Andrew; Ginanto, Dion
ABSTRACT: We used Latina/Latino Critical Race Theory (LatCrit) to re-analyze survey and interview data from earlier research in which we found that Latina/o students reported less positive experiences than other students in this high school. We found racial injustice in class enrollments, in students' experiences with stereotypes and prejudice, in student-teacher relationships, and in school policies and norms. LatCrit principles illustrate interconnections among racism, interest convergence, and colorblindness that create racial injustice for Latinas/os. We argue that counterstorytelling could emerge to resist that injustice and that educators must understand how racism functions in their schools and interrogate relevant policies and norms.